Novel therapeutic approaches targeting endotypes of severe airway disease. (3rd October 2021) - De Filippo, Maria; Votto, Martina; Licari, Amelia; Pagella, Fabio; Benazzo, Marco; Ciprandi, Giorgio; Marseglia, Gian Luigi
ABSTRACT: Introduction : Severe asthma and chronic rhinosinusitis (CRS), with nasal polyps (CRSwNP) and without nasal polyps (CRSsNP), are heterogeneous diseases characterized by different mechanistic pathways (endotypes) and variable clinical presentations (phenotypes). Areas covered : This review provides the clinician with an overview of the prevalence and clinical impact of severe chronic upper and lower airways disease and suggests a novel therapeutic approach with biological agents with possible biomarkers. To select relevant literature for inclusion in this review, we conducted a literature search using the PubMed database, using terms 'severe airways disease' AND 'endotype' AND 'treatment.' The literature review was performed for publication years 2010–2020, restricting the articles to humans and English language publications. Expert opinion : The coronavirus disease (COVID-19) pandemic has brought forth many challenges for patients with severe airway disease and healthcare practitioners involved in care. These patients could have an increased risk of developing severe SARS-CoV-2 disease, although treatment with biologics is not associated with a worse prognosis. Eosinopenia on hospital admission plays a key role as a diagnostic and prognostic biomarker.